Dynamic evolution process of turbulent channel flow after opposition control *Project supported by the National Natural Science Foundation of China (Grant No. 11402088 and Grant No. 51376062), State Key Laboratory of Alternate Electrical Power System with Renewable Energy Sources (Grant No. LAPS15005), and 'the Fundamental Research Funds for the Central Universities' (Grant No.2014MS33). (14th November 2016) - Ge, Mingwei; Tian, De; Yongqian, Liu
Abstract: Dynamic evolution of turbulent channel flow after application of opposition control (OC), together with the mechanism of drag reduction, is studied through direct numerical simulation (DNS). In the simulation, the pressure gradient is kept constant, and the flow rate increases due to drag reduction. In the transport of mean kinetic energy (MKE), one part of the energy from the external pressure is dissipated by the mean shear, and the other part is transported to the turbulent kinetic energy (TKE) through a TKE production term (TKP). It is found that the increase of MKE is mainly induced by the reduction of TKP that is directly affected by OC. Further analysis shows that the suppression of the redistribution term of TKE in the wall normal direction plays a key role in drag reduction, which represses the wall normal velocity fluctuation and then reduces TKP through the attenuation of its main production term. When OC is suddenly applied, an acute imbalance of energy in space is induced by the wall blowing and suction. Both the skin-friction and TKP terms exhibit a transient growth in the initial phase of OC, which can be attributed to the local effect of ⟨ v ′ v ′⟩ and ⟨− u ′ v ′⟩ in the viscous sublayer.